The Process for Determining the Beginning of the Iddah Period for Widows Who Want to Remarry: Conceptual of Learning Islamic Law - Nur Isnaini Farida; Syamsuddin (CV. Creative Tugu Pena, 2024)
The determination of the beginning of the iddah period for widows who wish to remarry is a crucial process governed by Islamic law. However, its implementation often encounters various challenges involving social dynamics, economic conditions, and public understanding of Islamic law. This study aims to explore how the Office of Religious Affairs (KUA) of Nogosari Subdistrict, Boyolali Regency, determines the beginning of the iddah period and manages the differences in views and challenges that arise during the process. This research employs a descriptive qualitative method with an approach of observation and in-depth interviews with key informants, including the head of the KUA, the marriage registrar, religious counselors, and administrative staff. The results show that KUA Nogosari strives to balance the requirements of Islamic law with the socio-economic realities of the community. The KUA faces challenges such as administrative limitations, differing community views, and the economic pressures experienced by widows. Nevertheless, the KUA has managed these challenges through enhanced education, administrative efficiency, and collaboration with various parties. In conclusion, KUA Nogosari has been able to perform its duties while considering the principles of justice and legal certainty, despite the complex challenges faced.